MODEL PEMBELAJARAN BLENDED/HYBRID UNTUK MENINGKATKAN KETERAMPILAN PRAKTIK DI TVET: STUDI LITERATUR SISTEMATIS - Hirval Hirval; Yusma Elda; Sovandi Marwan; Nizwardi Jalinus; Muhammad Anwar (STKIP Pesisir Selatan, 2025)
Objective: Technical and Vocational Education and Training (TVET) plays a crucial role in developing practical skills aligned with industry needs. However, practical learning in TVET often faces challenges such as limited facilities, high operational costs, and a gap between curricula and workplace standards. In the context of digital transformation, blended and hybrid learning models have emerged as innovative solutions that integrate online and face-to-face instruction to strengthen practical skill acquisition. This study systematically synthesizes the application of blended/hybrid learning models in TVET, focusing on identifying the models used, their impact on practical skills, and key implementation factors. Following the PRISMA framework, the review analyzes literature from Scopus, Web of Science, ERIC, and Google Scholar published between 2014 and 2024. Findings show that models such as flipped classroom, rotation model, and enriched virtual model have been variably implemented across global TVET institutions. Blended/hybrid learning has proven effective in enhancing learners’ practical skills—including procedural accuracy, work quality, and workplace safety—provided it is supported by well-structured pedagogical design, adequate digital infrastructure, educator readiness, and strong industry partnerships.